Effect of hydrophobic corrosion inhibitor on the cement hydration and leaching resistance of shotcrete - Wei Wang; Junsong Chen; Shuang Zhao; Luping Zeng; Jingshun Cai; Song Mu; Jinxiang Hong; Min Qiao (Case Studies in Construction Materials)
In some water-rich mountain tunnels and submarine tunnels, the primary lining shotcrete often suffers from calcium leaching damage. This study designs a hydrophobic corrosion inhibitor mainly composed of hydrophobic ingredients and nanoparticles, and explores its impact on the cement hydration and leaching resistance of shotcrete. Isothermal calorimetry, XRD, TG-DTG and SEM were performed on accelerated cement pastes, and the outcomes demonstrate that the incorporation of hydrophobic corrosion inhibitor could play a role in delaying hydration process, which was mainly attributed to the adsorption and complexation of carboxyl groups. Based on indoor accelerated leaching test, hydrophobic corrosion inhibitor could enhance the long-term compressive strength development stability in corrosion solution and avoid the phenomenon of shrinkage in the later stage. In addition, hydrophobic corrosion inhibitor could effectively diminish the leaching amount of calcium ions, thereby suppressing the precipitation of corrosion products such as calcium sulfate crystals. Moreover, hydrophobic corrosion inhibitor could reduce the water absorption rate and chloride ions diffusion coefficient of shotcrete specimens, indicating its excellent hydrophobicity. In the alkaline environment of cement hydration, the hydrolysis products of organic carboxylic acid esters in hydrophobic corrosion inhibitor reacted with calcium ions in hydration products system to generate nano calcium carboxylate particles, which blocking the micro- and nano-scale pores to enhance the compactness and hydrophobicity of shotcrete matrix. Insights and suggestions for addressing the issue of calcium leaching in shotcrete can be derived from the results of this research.